Chronic Central Serous Chorioretinopathy in Elderly Subjects: Structure and Blood Flow Characteristics of Retina and Choroid - Liu, Pei; Fang, Haixin; An, Guangqi; Jin, Bo; Lu, Chenyu; Li, Shu; Yang, Fan; Du, Liping; Jin, Xuemin (Ophthalmology and therapy, 2024)
Introduction With advancements in imaging technology, researchers have been able to identify more distinctive imaging features of central serous chorioretinopathy (CSC). However, existing research primarily concentrates on young patients aged 50 years and below, leaving a dearth of studies on elderly CSC patients. Previous studies indicate that elderly CSC patients may exhibit unique imaging characteristics and have a clinical prognosis that significantly differs from younger patients. This study aimed to evaluate the characteristics of retina, choroid structure, and blood flow in elderly patients with chronic CSC (cCSC) examined multimode imaging and try to find new pathogenesis information of it. Methods Using a cut-off age of 50 years, patients with chronic central serous chorioretinopathy were divided into two groups: older and younger. The control group consisted of 40 healthy individuals, with their right eyes assigned. Various clinical features were recorded, including the incidence of ellipsoid zone rupture (EZ-), fibrin in the subretinal fluid (SRF), pachydrusen, subretinal drusenoid deposits (SDD), pigment epithelial detachment (PED), double-layer sign (DLS), and choroidal lipid globule cavern. Measurements were taken for the thickness of the outer nuclear layer (ONL), the length of the extended outer photoreceptor segment (POS), the height and width of SRF, the vascular density of each layer of the retinal capillary plexus, the central macular thickness (CMT), and the subfoveal choroidal thickness (SFCT). Results The proportion of females in the elderly group (43.75%) was significantly higher than that in the youth group (22.41%) ( p = 0.034). The degree of hyperopia in the elderly group (1.03 ± 0.73) was higher than that in the youth group (0.26 ± 1.06), with a significant difference in BCVA ( p = 0.05). The thickness of SFCT, CMT, ONL in the elderly group, and the length of photoreceptor outer segment in the elderly group were thinner than those in the youth group ( p < 0.05). Choroidal capillary perfusion area (CCPA), macular area, and paramacular area were lower in the elderly group than those in the youth group in the full scan range ( p < 0.05). The blood flow densities of deep capillary plexus (DCP), intermediate capillary plexus (ICP), and superficial capillary plexus (SCP) in the whole scan range, macular area, and paramacular area were lower in the elderly group than in the youth group, but the differences were not statistically significant. Conclusions In conclusion, our data suggest that elderly patients with cCSC may experience different disease outcomes. Elderly cCSC patients exhibit less gender bias, poorer vision, more severe structural damage and ischemia in the choroid and retina, and have a higher risk of developing choroidal neovascularization.